Comparison Analysis Performance Of Honda Jazz Using Active VTec System And Non-Active VTec System Engine - Sanjaya, Dhanil (2012)
The objective of this research is to know the influence variable valve timing of engine performance of Honda Jazz. Research uses four stroke engine with two types of engine use active vtec system and engine not active vtec system. Use dynamometer to know that performance of Honda Jazz. Tools preparation step is conducted to prepare the entire tools that are used in the test. First step is we use Honda Jazz with SOHC VTEC. We test of performance Honda Jazz engine with active SOHC VTEC system on dyno test. For the first test, ECM of the car active so when the beginning vtec will active. Second test, non-activated the ECM so when vtec will not active, so there is no signal and the hydrolic oil to solenoid cannot move so that pin on cam also does not working. The mechanism of VTEC will different between active and not active. On rotation 4960 rpm, the highest torque generated by active vtec system is 124.6 Nm and non active vtec is 118.2 Nm. On rotation 6080 rpm, the highest power generated by active vtec system is 94.5 Nm and non active vtec is 87.2 Nm. Increase number of air-fuel mixture in combustion chamber which can make performance will increases.